A Performance Analysis Of The Veterinary Teaching Hos-pital Of Universitas Brawijaya Using The Balanced Score-card Method - Ayu, Sherinda; Adam, Helmy (Telaah Ilmiah Akuntansi dan Perpajakan, 2026)
This study aims to describe the performance of RSHP UB using the Balanced Scorecard. This study applies a quantitative approach, using primary data from RSHP UB Financial Statements for 2021 to 2023, inpatient data for 2021 to 2023, and other sources. The results of this study exhibit that the performance of the RSHP UB is categorised as moderate or fairly good (BB category) with a total score of 49%. Based on the results of the analysis, from a financial perspective, RSHP UB does not show good performance; from a customer perspective, it shows excellent results in customer satisfaction and is fairly good for customer retention and customer acquisition despite the need for improvement; from an internal business perspective, it has reached the ideal level of ALOS but is not suitable in BTO and BOR; and from growth and development perspective, it has obtained a very good result.